Podemos conhecer nossas próprias emoções? Uma reconstrução crítica das teorias do autoconhecimento emocional e defesa do agencialismo - Barcelos, Róbson da Rosa (2023)
This thesis examines the problem of emotional self-knowledge. Two fundamental tasks are developed in it: the understanding of emotional self-knowledge from the perspective that recognizes the complexity of emotions and the evaluation of three theories of self-knowledge (introspectivism, inferentialism and agentialism). From the indication of the problem of emotional self-knowledge, a critical analysis of the introspective, inferentialist and agencialist theory of self-knowledge is developed, seeking to highlight the superiority of the agencialist theory in relation to the others. In the first chapter, the challenges of emotional self-knowledge and Peter Goldie's theory are addressed, which understands emotions as complex entities, involving feelings towards and with a narrative structure. This perspective will be used to discuss emotional self-knowledge. The second chapter examines the introspective theory of emotional self-knowledge, highlighting its limitations pointed out by Eric Schwitzgebel and Richard Moran, which make it inadequate to explain emotional self-knowledge. In the third chapter, the inferential explanation of the knowledge of one's own emotions is analyzed as well as its criticisms, concluding that this approach is also not satisfactory. In the fourth chapter, Richard Moran's agencialist approach is presented, harshly criticized by Naomi Kloosterboer and adjusted by Victoria McGeer. They highlight the role of the agent in expressing and understanding one's own emotions, suggesting that it is more appropriate to explain emotional self-knowledge. Therefore, approaching the role of the agent in the process of emotional self-knowledge through agencialist theory is more appropriate to explain the complex phenomenon of emotional self-knowledge. Thus, the thesis contributes to the development of a more comprehensive theory of emotional self-knowledge, providing a critical analysis of existing theories and highlighting the relevance of the agential model in understanding emotions and how we understand and express them.